Corticomotor Plasticity Predicts Clinical Efficacy of Combined Neuromodulation and Cognitive Training in Alzheimer’s Disease - Brem, Anna-Katharine; Di Iorio, Riccardo; Fried, Peter J.; Oliveira-Maia, Albino J.; Marra, Camillo; Profice, Paolo; Quaranta, Davide; Schilberg, Lukas; Atkinson, Natasha J.; Seligson, Erica E.; Rossini, Paolo Maria; Pascual-Leone, Alvaro (Frontiers in Aging Neuroscience, 2020)
Objective To investigate the efficacy of repetitive transcranial magnetic stimulation (rTMS) combined with cognitive training for treatment of cognitive symptoms in patients with Alzheimer’s disease (AD). A secondary objective was to analyze associations between brain plasticity and cognitive effects of treatment. Methods In this randomized, sham-controlled, multicenter clinical trial, 34 patients with AD were assigned to three experimental groups receiving 30 daily sessions of combinatory intervention. Participants in the real/real group (n = 16) received 10 Hz repetitive transcranial magnetic stimulation (rTMS) delivered separately to each of six cortical regions, interleaved with computerized cognitive training. Participants in the sham rTMS group (n = 18) received sham rTMS combined with either real (sham/real group, n = 10) or sham (sham/sham group, n = 8) cognitive training. Effects of treatment on neuropsychological (primary outcome) and neurophysiological function were compared between the 3 treatment groups. These, as well as imaging measures of brain atrophy, were compared at baseline to 14 healthy controls (HC). Results At baseline, patients with AD had worse cognition, cerebral atrophy, and TMS measures of cortico-motor reactivity, excitability, and plasticity than HC. The real/real group showed significant cognitive improvement compared to the sham/sham, but not the real/sham group. TMS-induced plasticity at baseline was predictive of post-intervention changes in cognition, and was modified across treatment, in association with changes of cognition. Interpretation Combined rTMS and cognitive training may improve the cognitive status of AD patients, with TMS-induced cortical plasticity at baseline serving as predictor of therapeutic outcome for this intervention, and potential mechanism of action. Clinical Trial Registration www.ClinicalTrials.gov, identifier NCT01504958.